2011
DOI: 10.1007/s10194-011-0322-8
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of pain perception by transcranial magnetic stimulation of left prefrontal cortex

Abstract: Evidence by functional imaging studies suggests the role of left dorsolateral prefrontal cortex (DLPFC) in the inhibitory control of nociceptive transmission system. Repetitive transcranial magnetic stimulation (rTMS) is able to modulate pain response to capsaicin. In the present study, we evaluated the effect of DLPFC activation (through rTMS) on nociceptive control in a model of capsaicin-induced pain. The study was performed on healthy subjects that underwent capsaicin application on right or left hand. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 39 publications
2
92
3
1
Order By: Relevance
“…Instead, active DLPFC tDCS increased FC between VPL and M1. Our findings, in part, challenge a classical notion that suggests that DLPFC is a region primarily involved in processing emotional-affective information (Brighina et al, 2011;Garcia-Larrea et al, 2003;Lorenz et al, 2003). Here instead, we highlight that stimulation of DLPFC can modulate FC between VPL and M1.…”
Section: Fc Changes Across Sensory Networkcontrasting
confidence: 47%
See 2 more Smart Citations
“…Instead, active DLPFC tDCS increased FC between VPL and M1. Our findings, in part, challenge a classical notion that suggests that DLPFC is a region primarily involved in processing emotional-affective information (Brighina et al, 2011;Garcia-Larrea et al, 2003;Lorenz et al, 2003). Here instead, we highlight that stimulation of DLPFC can modulate FC between VPL and M1.…”
Section: Fc Changes Across Sensory Networkcontrasting
confidence: 47%
“…While subjects rested their hands, we used visual confirmation of contraction of the left first dorsal interosseous muscle to finalize our motor hotspot in right M1. Similarly, for DLPFC tDCS, center of the anodal electrode was placed over the right DLPFC, localized to a point 5 cm anterior to the coordinates of the motor hotspot in right M1, as outlined in previous studies (Brighina et al, 2011;Graff-Guerrero et al, 2005;Pascual-Leone et al, 1996) (Fig. 2A).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a few recent pain studies have used rTMS technology to identify the role played by the DLPFC. [23][24][25][26][27] For example, Nahmias et al 27 showed that unilateral, high frequency rTMS pulses applied to the right DLPFC produced diffuse analgesic effects in healthy human participants exposed to experimental heat and cold pain. This initial result suggests that the DLPFC may, indeed, play a causal role in reducing painful sensations.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations utilizing transcranial direct current stimulation (tDCS) and repetitive transcranial magnetic stimulation (rTMS) provided initial evidence that DLPFC stimulation may have a role in decreasing pain reports (Boggio et al, 2009;Borckardt et al, 2006;Brighina et al, 2011) and increasing pain tolerance (Borckardt et al, 2007;Lefaucheur et al, 2008;Mylius et al, 2012). A potential mechanism for some of these findings is the modulation of DLPFC interhemispheric connectivity (interactions among the left DLPFC (lDLPFC) and right DLPFC (rDLPFC) across the corpus callosum).…”
Section: Introductionmentioning
confidence: 99%